2012
DOI: 10.1590/s1516-35982012000600028
|View full text |Cite
|
Sign up to set email alerts
|

Energy and protein nutritional requirements for Nellore bulls

Abstract: -The objective of this study was to determine the nutritional requirements of energy and protein and estimate the efficiencies of metabolizable energy utilization for fat and protein deposition, as well as for maintenance (k m ) and growth (k g ). An experiment of comparative slaughter was carried out with thirty-seven 14-month-old (±1 month) Nellore bulls with 259±24.9 kg. Animals were divided as follows: five to reference, four to maintenance level and twentyeight bulls feeding ad libitum. Bulls were also g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…The estimated value of k gain was close to that described by Menezes et al (2016) and Costa e Silva et al (2012), 34.4% and 33.0%, respectively. However, Chizzotti et al (2008) described in a meta‐analyses a value of 44% for k gain , a value eight percentage units higher than that found in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The estimated value of k gain was close to that described by Menezes et al (2016) and Costa e Silva et al (2012), 34.4% and 33.0%, respectively. However, Chizzotti et al (2008) described in a meta‐analyses a value of 44% for k gain , a value eight percentage units higher than that found in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The retained energy, determined from the empty body composition of the animals, increased with feed intake and weight gain, while the quantity of deposited energy as protein decreased with the increase in weight gain, consistent with findings of previous reports (CHIZZOTTI et al, 2007;SILVA et al, 2012).…”
Section: Eqsupporting
confidence: 91%
“…An increase in the lactic acid content results in a decrease in the pH value which inhibits the proliferation of harmful bacteria that require a large consumption of nutrients and helps in the retention of nutrients such as CP [ 20 , 21 ]. It has been reported that ruminants require more than 70 g/kg DM CP content in their feed to ensure normal ruminal microbial activity, and low CP content may reduce the proliferation of rumen microbes [ 22 ]. In this study, both the CP content of the C25 and R25 groups complied with the requirements (78.9 and 75.4 g/kg DM, respectively) and benefited from the abundant protein in the SCR.…”
Section: Discussionmentioning
confidence: 99%